2017
DOI: 10.4014/jmb.1703.03080
|View full text |Cite
|
Sign up to set email alerts
|

Designing Signal Peptides for Efficient Periplasmic Expression of Human Growth Hormone in Escherichia coli

Abstract: The secretion efficiency of a protein in a Sec-type secretion system is mainly determined by an N-terminal signal peptide and its combination with its cognate protein. Five signal peptides, namely, two synthetic Sec-type and three alpha-amylase-derived signal peptides, were compared for periplasmic expression of the human growth hormone (hGH) in. Based on in silico predictions on the signal peptides' cleavage efficiencies and their corresponding mRNA secondary structures, a number of amino acid substitutions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…61 For pelB WT and variants, mRNA sequence including the ribosome binding site (RBS), translation start codon, signal sequence, and six nucleotides after the end of the signal peptide-coding region (104 bases total) was analyzed to predict its possible secondary structure and the folding free energy (ΔG). 51,52,62 ■ RESULTS AND DISCUSSION Construction of the Secretory Expression Vector and the Expression of Extracellular PETase in E. coli BL21-Gold (DE3). The gene fragment encoding PETase was cloned into the expression vector pET22b, which contains the signal peptide, pelB, upstream of the multiple cloning site.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…61 For pelB WT and variants, mRNA sequence including the ribosome binding site (RBS), translation start codon, signal sequence, and six nucleotides after the end of the signal peptide-coding region (104 bases total) was analyzed to predict its possible secondary structure and the folding free energy (ΔG). 51,52,62 ■ RESULTS AND DISCUSSION Construction of the Secretory Expression Vector and the Expression of Extracellular PETase in E. coli BL21-Gold (DE3). The gene fragment encoding PETase was cloned into the expression vector pET22b, which contains the signal peptide, pelB, upstream of the multiple cloning site.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…This module makes it possible to display an amino acid that is located on sequence in the position 1-10 both from C-terminus and from N-terminus. It can be helpful for an analysis and designing of signal peptides [7] and for applying the N-end rule. According to this rule the second N-terminal amino acid of a protein determines its half-life [8].…”
Section: Aminoacid Positionmentioning
confidence: 99%
“…Five different signal peptides were identified by literature search and fused with the codon-optimized mature IL-21 [16][17][18][19]. The origin and amino acid sequence of signal peptides are shown in Table 1.…”
Section: Signal Peptide Optimizationmentioning
confidence: 99%
“…A number of parameters, including codon usage, mRNA stability and the GC content, and RNA instability motifs and splicing sites, are considered for gene optimization to improve transcription, translation, and folding of recombinant protein [15,16]. The selection of proper signal peptides is also critical for establishing a manufacturing process for protein production to improve the correct processing and secretion of recombinant proteins through the transport of the translated proteins into the endoplasmic reticulum [17,18]. Recent studies have demonstrated the effectiveness of different signal peptides on the production of recombinant protein in CHO cells [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%